A Refined Short-term Scheduling Method Considering the Difference of Peak-shaving Performance of Hydropower Stations - HUANG Kui; CHENG Ruixiang; HU Jiaqiu; LI Xiangyang; ZHU Yunke; WU Xinyu (Renmin Zhujiang)
The scale of regulated hydropower in the power grid and the demand for refined dispatch continue to expand.How to carry out refined peak-shaving considering the differences in the regulatory performance of different power stations,which makes thermal power run smoothly and reduces the depth of participation in peak shaving,is the key problem to be solved in short-term hydropower dispatch of the power grid.To deal with the refined short-term scheduling of some provincial power grids,this paper proposes a peak-shaving optimization model of hydropower station groups considering peak-shaving performance differences.The model makes the short-term scheduling plan more accurate and reasonable and can better use hydropower regulation capacity.According to the different regulatory performance of the hydropower stations under the power grid,the paper conducts differentiated constraint processing to the weak peak-load station,the peak-load station,and the balanced power station.In addition,the successive associated search method is applied to solve the differentiated peak load optimization model.A total of 37 hydropower stations in Guangxi power grid are selected for the case study.The results show that compared with the traditional model,the differential peak-shaving optimization model takes into account the difference in regulation performance of different hydropower stations.It further reduces the peak-valley difference of the residual load of the system,smooths the fluctuation of the residual load of the system,and levels the small and frequent fluctuations of the system load,which is a fine scheduling method to meet the actual engineering requirements.